Large Thermal Conductivity Switch Ratio in Barium Titanate Under Electric Field through First‐Principles Calculation. Issue 12 (11th September 2018) - Liu, Chenhan; Mishra, Vivek; Chen, Yunfei; Dames, Chris
Abstract: The thermal conductivity of crystalline materials is typically one or two orders of magnitude higher than that of their amorphous structures. The phase transition in barium titanate is generally considered to exhibit order–disorder character, suggesting the potential for thermal conductivity switching if this order–disorder transition can be controlled. To investigate this possibility computationally, following the method of Fu and Bellaiche, here electric fields are applied to align the polarizations and transform disordered paraelectric structures to ordered ferroelectric structures. Solving the Boltzmann transport equation, the theoretical limit of a perfectly disordered structure is found to have thermal conductivity of a factor of 3.9 lower than the perfectly ordered structure. The thermal conductivity of the ordered structure can be further enhanced by up to another 2.4 times under electric fields due to the reduction in phonon scattering rates, implying a theoretical maximum thermal conductivity switching ratio of 9.4. This study yields two guidelines in searching for high thermal conductivity switch ratio in ferroelectric materials: the structure should be single domain under electric field and the phase transition should be fully order–disorder rather than displacive. Abstract : Applying strong electric fields to a ferroelectric material having order–disorder phase transition can transform its structure from disordered to ordered, reminiscent of an amorphous–crystalline transition. First‐principles calculations of this effect in barium titanate show a thermal conductivity switching ratio of up to 9.4 comparing perfectly ordered and disordered states, suggesting a mechanism for electric field controlled solid‐state thermal switch.